Family therapy with the experts behavioral couples therapy - Governors State University; Allyn and Bacon Professional ([S.I] : Allyn and Bacon Professional, 1998)
This video series features the theories of family therapy and counseling with real clients, real issues, and today's leading family therapist
Editor, Judy Filer
Keywords: Family therapists